2004
DOI: 10.1529/biophysj.103.033803
|View full text |Cite
|
Sign up to set email alerts
|

Mesoscopic Structure in the Chain-Melting Regime of Anionic Phospholipid Vesicles: DMPG

Abstract: In a range of low ionic strength, aqueous dispersions of the anionic phospholipid DMPG (dimyristoylphosphatidylglycerol) have a transparent intermediate phase (IP, between T(m)(on) congruent with 20 degrees C and T(m)(off) congruent with 30 degrees C) between the turbid gel and fluid membrane phases, evidenced in turbidity data. Small angle x-ray scattering results on DMPG dispersions show that, besides the bilayer peak present in all phases, a peak corresponding to a mesoscopic structure at approximately 400 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

25
127
0
16

Year Published

2005
2005
2017
2017

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 55 publications
(168 citation statements)
references
References 40 publications
(78 reference statements)
25
127
0
16
Order By: Relevance
“…SAXS patterns in the gel and fluid phases show an isotropic ring suggesting that DMPG forms spherical vesicles as expected [3,7,17]. Broad peak is a characteristic of single bilayer membranes [3,18]. In the intermediate phase at T = 22 and 24°C, on the other hand, anisotropic rheo-SAXS patterns are obviously observed.…”
Section: Rheo-saxsmentioning
confidence: 60%
See 4 more Smart Citations
“…SAXS patterns in the gel and fluid phases show an isotropic ring suggesting that DMPG forms spherical vesicles as expected [3,7,17]. Broad peak is a characteristic of single bilayer membranes [3,18]. In the intermediate phase at T = 22 and 24°C, on the other hand, anisotropic rheo-SAXS patterns are obviously observed.…”
Section: Rheo-saxsmentioning
confidence: 60%
“…However, electron spin resonance (ESR) experiments demonstrated that the lipid monomers were not exchanged between vesicles, which did not support the existence of the sponge phase [11]. Other proposed model raised by SAXS data analysis suggests that new lamellar phase with pores or porous spherical vesicle is the most plausible structure [3,7,10,12,13]. Appearance of such intermediate structure during the chain-melting transition motivated us to characterize the phase behavior of DMPG systems by the use of a rheo-physical method, a *Current address: Division of Applied Physics, Graduate School of Engineering, Hokkaido University, N13W8, Sapporo 060-8628, Japan E-mail: sfujii@eng.hokudai.ac.jp combination of rheology and small angle X-ray scattering.…”
Section: Introductionmentioning
confidence: 94%
See 3 more Smart Citations